1999
DOI: 10.1016/s0014-5793(99)01683-x
|View full text |Cite
|
Sign up to set email alerts
|

Disulfide structure of the pheromone binding protein from the silkworm moth, Bombyx mori

Abstract: Disulfide bond formation is the only known posttranslational modification of insect pheromone binding proteins (PBPs). In the PBPs from moths (Lepidoptera), six cysteine residues are highly conserved at positions 19, 50, 54, 97, 108 and 117, but to date nothing is known about their respective linkage or redox status. We used a multiple approach of enzymatic digestion, chemical cleavage, partial reduction with Tris-(2-carboxyethyl)phosphine, followed by digestion with endoproteinase Lys-C to determine the disul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
153
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 225 publications
(165 citation statements)
references
References 36 publications
12
153
0
Order By: Relevance
“…5, which is published as supporting information on the PNAS web site), which is involved in the formation of the C-terminal ␣-helix (MDVAVGEILAE) (18). The molecular mass of BmorPBP⌬P129-V142 obtained by LC-ESI͞MS (observed, 14,466 Da; calculated, 14,472 Da) indicated that all Cys residues were linked to form three disulfide bridges, as in the native conformation (18)(19)(20)(21)(22). CD data (see Fig.…”
Section: Resultsmentioning
confidence: 98%
“…5, which is published as supporting information on the PNAS web site), which is involved in the formation of the C-terminal ␣-helix (MDVAVGEILAE) (18). The molecular mass of BmorPBP⌬P129-V142 obtained by LC-ESI͞MS (observed, 14,466 Da; calculated, 14,472 Da) indicated that all Cys residues were linked to form three disulfide bridges, as in the native conformation (18)(19)(20)(21)(22). CD data (see Fig.…”
Section: Resultsmentioning
confidence: 98%
“…OBPs are synthesised in the accessory cells surrounding neurons and are subsequently secreted into the hydrophilic extracellular space. These proteins are characterised by a specific domain that comprises six a-helices joined by three disulphide bonds (Leal et al, 1999;Scaloni et al, 1999). Although the specific physiological roles of OBPs are not well established, it is believed that they act as molecular carriers that transport and deliver odorants to chemor- …”
Section: Insect Chemosensory Gene Familiesmentioning
confidence: 99%
“…CSPs are more conserved, with a specific motif of four cysteines that form two disulphide bridges between neighbouring residues. This arrangement differs from that of OBPs, in which disulphide bridges are inter-helical and make two small loops to form a more rigid structure Leal et al, 1999;Scaloni et al, 1999). However, some CSPs can be identified by Hidden Markov Model (HMM)-based searches using information from the OBP sequence alignment as a statistical descriptor.…”
Section: Insect Chemosensory Gene Family Evolutionmentioning
confidence: 99%
“…The first study concluded that the PBPs could exist in alternate redox states (24). PBPs have six highly conserved cysteine residues (25)(26)(27), which form three disulfide bridges (28,29). In a model resulting from the first study, the lower affinity reduced form releases or presents the pheromone and shifts to a higher affinity oxidized form upon interaction with the dendritic membrane (20).…”
mentioning
confidence: 99%